Effects of intrathecal amylin on formalin-induced nociception and on cAMP accumulation in the rat embryonic spinal cells. (June 2016) - Khoshdel, Zahra; Takhshid, Mohammad Ali; Owji, Ali Akbar
Abstract: Amylin (AMY) is a member of calcitonin family of peptides. In this study, the effects of intrathecal (i.t) injection of AMY on the inflammatory pain and on the cAMP accumulation in the rat spinal cells were investigated. By using AMY receptor antagonists, we also studied the pharmacology of AMY receptors in the spinal cells. Formalin model of inflammatory pain was induced by intraplantar injection of formalin. AMY (0.06250–2500 pmol/rat) was administrated i.t 15 min before the injection of formalin. Antagonists were injected i.t 10 min before the injection of AMY and/or morphine. AMY reduced formalin-induced pain in a dose dependent mode. This effect was inhibited by the potent AMY antagonist, AC187 but not CGRP8-37 . rAMY8-37, most commonly reported as a weak AMY antagonist, showed to be equally or more potent than AC187 in antagonizing the above effects. The opioid antagonist, naloxone, had no significant effects on AMY antinociceptive effects. Primary dissociated cell culture was used to investigate the effect of AMY on cAMP production and to characterize AMY receptors in the spinal cells. AMY moderately increases cAMP accumulation in the spinal cells with an EC50 value of 74.62 nM. This effect was not affected by CGRP8-37 but was inhibited by AC187 and rAMY8-37 with pA2 values of 7.94 and 7.87 respectively. In conclusion, effects of AMY in reducing formalin induced pain and on the cAMP accumulation by spinal cells are mediated through undefined receptors. Highlights: Intrathecal administration of amylin reduced formalin-induced pain in rats. Amylin increased accumulation of cAMP in the rat spinal cells. AMY8 -37 and AC187 blocked the effects of AMY on nociception and cAMP accumulation. CGRP8 -37 failed to inhibit the effects of AMY on nociception and cAMP accumulation.